ERROR ANALYSIS ON THE ESTIMATION OF CUMULATIVE INFILTRATION SOIL USING GREEN AND AMPT MODEL - Muhamad Askari; Satyanto Krido Saptomo; Budi Indra Setiawan (PERTETA, 2006)
ABSTRACT Green and Ampt infiltration model is still useful for the infiltration process because of a clear physical basis of the model and of the existence of the model parameter values for a wide range of soil. The objective of thise study was to analyze error on the esimation of cumulative infiltration in sooil using Green and Ampt model and to design laboratory experiment in measuring cumulative infiltration. Parameter of the model was determined based on soil physical properties from laboratory experiment. Newton –Raphson method was esed to estimate wetting front during calculation using visual Basic for Application (VBA) in MS Word. The result showed that Dq contributed the highest error in estimation of cumulative infiltration and was followed by K, H0, H1, and t respectively. It also showed that the calculated cumulative infiltration is always lower than both measured cumulative infiltration and volumetric soil water content. Keyword: Green and Ampt, cumulative infiltration, wetting front, VB Application.